THE USE OF NEW INFORMATION TECHNOLOGY IN TEACHING CHEMISTRY - Sodiqov Murodjon (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article analyzes the issues of the use of new information technologies in the teaching of chemistry.